The Discourse of the Intellectuals and Violence in the Algerian novel: The Case of Memory of Water by Wasiny Aredj - Esmail Naderi; bibi rahil sensebli; mohammad mehdi roshan (دراسات في اللغة العربيّة وآدابها)
Due to the political, religious and social factors in the post-colonial period, Algeria witnessed a violence which claimed the lives of thousands of Algerians. The academics and intellectuals were among the victims who were most frequently targeted by this violence. This experience is reflected in the literary works. They show this nation’s tragic experience by combining reality and imagination. This article is based on a study of the phenomenon of violence and its manifestations in the intellectual and dialogic discourse of the novel, the Memory of Water by Wasiny Laredj, the  contemporary Algerian novelist. In this study, the descriptive-analytical method has been used. The result of the analysis indicates that the violence brought up in this novel are of political, religious, sexual and types in a colonialist context. The disparate reactions of intellectuals to violence is as follows: commitment, opportunity, silence, neutrality or immigration. The occurrence of violence can be noticed from the atmosphere of the novel, its language, and the characters’’ memories, and dreams.